An Updated List of Odonata Species from Athgarh Forest Division, Odisha, Eastern India (Insecta: Odonata) - Arajush Payra; Suraj Kumar Dash; Himanshu Shekhar Palei; Ashish D Tiple; Arun Kumar Mishra; Rabindra Kumar Mishra; Srusti Dhar Rout (Mongolian Journal of Biological Sciences, 2020)
Altogether 72 species of Odonata belonging to 46 genera and 9 families were recorded from Athgarh Forest Division, of which 32 species are representatives of the suborder Zygoptera and 40 species are members of the suborder Anisoptera. Athgarh Forest Division represents 65.4 % of the Odisha state and 14.7 % of the Indian Odonata fauna. Among recorded species, 17 species are newly recorded for Athgarh Forest Division. Elattoneura nigerrima Laidlaw, 1917 is reported for the first time from the state, and occurrence of Indothemis carnatica (Fabricius, 1798) in Odisha is confirmed here for the first time. Pseudagrion spencei Fraser, 1922 is also added to the Odonata fauna of Odisha and reported for the second time in the state from Athgarh Forest Division.